Novel IL-12Rβ1 deficiency-mediates recurrent cutaneous leishmaniasis. (November 2021) - Khattak, Farhad Ali; Akbar, Noor ul; Riaz, Maira; Hussain, Mubashir; Rehman, Khalid; Khan, Shahid Niaz; Khan, Taj Ali
Abstract: Background: The IL-12/IFN-γ axis plays a vital role in the control of intramacrophagic pathogens including Leishmania infections. Objective: The aim of this study was to investigate genetic defects in the IL-12/IFN-γ axis in cutaneous leishmaniasis patients, using immunological and genetic evaluation. Methods: Enzyme-linked immunosorbent assay was used to quantify IFN-γ, while flow cytometry was performed to analyze surface IL-12Rβ1/IL-12Rβ2 expression and phosphorylation of signal transducers as well as the activator of transcription 4 (pSTAT4). Sequencing was carried out for genetic analysis. Results: The peripheral blood mononuclear cells from the two patients (P1 and P2) demonstrated impaired production of IFN-γ. Furthermore, abolishment of the surface expression of Il-12Rβ1 was observed in lymphocytes, with consequent impairment of STAT4 phosphorylation in the lymphocytes of P1 and P2. IL-12Rβ1 deficiency was identified, which was caused by a novel homozygous missense mutation (c.485>T/p.P162L) and a novel homozygous nonsense mutation (c.805G>T/P.E269*) in the IL-12R β 2 gene of P1 and P2, respectively. In silico analyses predicted these novel mutations as being pathogenic, causing truncated proteins, with consequent inactivation. Conclusion: Our data have expanded the phenotype and mutation spectra associated with IL-12Rβ1 deficiency, and suggest that patients with CL should be screened for mutations in genes of the IL-12/IFN-γ axis.